Protein for sports-New data and new recommendations - Ziegenfuss, T. N.; Landis, J. A.; Lemieux, R. (Strength and Conditioning Journal, 2010)
ESTIMATION OF OPTIMAL PROTEIN AND/OR AMINO ACID INTAKE FOR PHYSICALLY ACTIVE INDIVIDUALS HAS BEEN HISTORICALLY PROBLEMATIC BECAUSE (A) SUBJECTS CONSUMING THE SAME ABSOLUTE AMOUNT OF PROTEIN COULD CONSUME DIFFERENT AMOUNTS AND TYPES OF AMINO ACIDS, (B) THE TIMING OF INGESTION (PRE VERSUS POST EXERCISE) ALTERS PROTEIN KINETICS (SYNTHESIS VERSUS BREAKDOWN), AND (C) THE ADDITION OF NONPROTEIN ENERGY (CARBOHYDRATE) AFFECTS PROTEIN KINETICS.